Biochar from wood waste as additive for structural concrete. (11th October 2021) - Sirico, Alice; Bernardi, Patrizia; Sciancalepore, Corrado; Vecchi, Francesca; Malcevschi, Alessio; Belletti, Beatrice; Milanese, Daniel
Highlights: Biochar collected from a wood waste pyro-gasification plant for energy generation. Biochar addition in structural concrete in 4 percentages, up to 10 % by wt. of cem. Influence of biochar on microstructure of the cement-based composite. Experimental evaluation of fresh and hardened physical and mechanical properties. Improvement of concrete mechanical properties for additions up to 5%. Abstract: The environmental impacts of cement and concrete industries are increasingly taken into consideration by regulatory agencies and new solutions must be found to turn into more sustainable productions. The use of waste materials as partial replacement of cement and/or aggregates or also as fillers into cement-based admixtures is a possible way to reduce the related negative impacts, such as carbon dioxide emissions and raw materials consumption. This work explores the possibility of using biochar, a carbon-rich and porous solid by-product resulting from thermochemical conversion of residual biomass under controlled conditions, as filler in concrete for structural use. The biochar used in this study derives from a commercial plant, which produces energy from pyro-gasification of woodchips. Biochar is at first chemically and morphologically characterized, then it is added as filler in concrete in different percentages, up to 10% by weight of cement. The effects of its introduction on fresh and hardened physical and mechanical properties of concrete, as well as on the internal matrix microstructure, are evaluated and compared to a reference concrete. Different curing conditions (wet and dry) and curing times (up to 365 days) are processed, also in order to evaluate biochar effect on concrete in terms of internal curing action and long-term behavior.